KOMUNIKASI DAN PENGENDALIAN KONFLIK DALAM POLITIK - Sukarno, Bedjo (Transformasi, 2014)
Presentation in communicating the message that accompanied with a sense of sincere andhonest. Expected to create a culture of mutual trust as a positive emotional entwined in thecommunication process very effective. In control, conflict management should be directed to theparties involved in the conflict in order to find a common understanding in diversity. To the roleof open communication in the reconciliation can be done as a sign of agreement and not leaveproblems in the future.Keywords: communication, conflict, management.